RISK FACTORS FOR INCIDENCE OF MEASLES IN THE HAMLET WANDU SALUBOMBA VILLAGE WORK AREA HEALTH CENTER DONGGALA - Juniarti, Juniarti; J.Kunoli, Firdaus; Afni, Nur (PROMOTIF: Jurnal Kesehatan Masyarakat, 2016)
ABSTRACTÂ Â Measles in Health Center Donggala increase from year 2014 - 2015 ie from 3 cases to 31 cases precisely in Hamlet Village Wandu Salubomba with incidence rate of 27.6%. Measles immunization coverage per year is not the UCI (<85%) and there are still many people who do not understand about balanced nutrition in the family as well as 35% of the villagers Salubomba children are in the age group 0-15 years were estimated susceptible to measles. These conditions allow a risk factor for the incidence of measles in the hamlet village Wandu Salubomba ie age, immunization status and nutritional status. This study aims to determine risk factors for incidence of measles in the hamlet Wandu Salubomba Village Health Center Donggala. Research is a kind of case control analytic approach that is by comparing the case group and the control group. The sample in this study is total cases: 31 patients and 31 children as controls. The results showed that age, immunization status and nutritional status is a risk factor incidence of measles with OR = 2.07 (CI = 0.17 to 24.0), OR 3.38 (CI = 1.18 to 9.7) and OR = 3.81 (CI = 1.33 - 10.9). This study suggested that Health Center should conduct more thorough counseling and continuing the Hamlet Village Wandu Salubomba particular and the whole society in Puskesmas Donggala in general in order to increase knowledge about measles Keywords: Age, Measles, Nutrition, Measles